Queermuseu: Discursos e Sentidos em Exposição - Zanella, Fábio Lúcio (2020)
The present study develops Discourse Analysis on the discourses and senses that circulated in the comments produced from the Queermuseu art exhibition that was held in Porto Alegre, RS, in 2017. The works in the exhibition referred to the discourses about the sexuality and religion, thus, it generated great repercussion in the media polemicizing the issue. Then Santander Bank, sponsor of the event, decided to close the exhibition on September 10, 2017 and made an explanatory note on the social network Facebook. With this publication, the Internet users made comments about the event and, in less than two days, there were more than 1,000 comments, reaching 30,000 comments published. Thus, this research aims to verify the discursive functioning of the comments linked to the note published by Santander that communicated the closing of the exhibition Queermuseu. To delimit the analysis, the first 1000 comments, published between September 10 and 11, 2017, were observed, and the twenty that had the most likes by Facebook users were selected. The theoretical basis and methodology are based on the French Orientation Discourse Analysis developed by Michel Pêcheux. In this theoretical field, it is studied how the discourses are put into circulation and how they work generating an effect of meaning for the subject, in addition, it deals with the functioning of ideological crossings and discursive regularities inserted in the discourses. With the realization, it was noticed the mobilization of several discursive formations that interwoven in the discursivization of comments show the regularity of the discourses and the positions in relation to the Queermuseu based on constituted memories (discursive, institutionalized and metallic). In cyberspace, circulation produces constant displacements and updates for Internet users, functioning as a space of plurality of opinions and effects of meaning from a metallic memory with a multiplicity of voices. With the study, it was noticed that there are interdictions about says in favor of the Queermuseu. The comments show the subject position through social networks, mainly by conservative segments, it is observed that there is a polarization effect potentiated by cyberspace because the subject can have the impression that there is a collective taking a position based on yourself discursive formation.